High-resolution 3D photopolymerization assisted by upconversion nanoparticles for rapid prototyping applications - Rocheva, Vasilina V. (Sci Rep, 2018)
Three-dimensional (3D) rapid prototyping technology based on near-infrared light-induced polymerization of photocurable compositions containing upconversion nanomaterials has been explored. For this aim, the rationally-designed core/shell upconversion nanoparticles NaYF(4):Yb(3+),Tm(3+)/NaYF(4), with the distinct ultraviolet-emitting lines and unprecedentedly high near-infrared to ultraviolet conversion efficiency of [Formula: see text] have been used. The upconverted ultraviolet photons were capable to efficiently activate photoinitiators contained in light-sensitive resins under moderate intensities of NIR excitation below 10 W cm(−2) and induce generation of radicals and photopolymerization in situ. Near infrared-activated polymerization process, both at the millimeter and sub-micron scales, was investigated. Polymeric macro- and microstructures were fabricated by means of near infrared laser scanning photolithography in the volume of liquid photocurable compositions with focused laser light at 975 nm wavelength. Examination of the polymerization process in the vicinity of the nanoparticles shows strong differences in the rate of polymer shell growth on flat and edge nanoparticle sides. This phenomenon mainly defines the resolution of the demonstrated near infrared - ultraviolet 3D printing technology at the micrometer scale level.